2014
DOI: 10.1038/ncomms4304
|View full text |Cite
|
Sign up to set email alerts
|

Potential climate engineering effectiveness and side effects during a high carbon dioxide-emission scenario

Abstract: The realization that mitigation efforts to reduce carbon dioxide emissions have, until now, been relatively ineffective has led to an increasing interest in climate engineering as a possible means of preventing the potentially catastrophic consequences of climate change. While many studies have addressed the potential effectiveness of individual methods there have been few attempts to compare them. Here we use an Earth system model to compare the effectiveness and side effects of afforestation, artificial ocea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
306
2
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 242 publications
(337 citation statements)
references
References 68 publications
27
306
2
2
Order By: Relevance
“…Counter-intuitively, afforestation at mid-latitudes and in northern, boreal forests may have a net warming effect, despite increasing the storage of carbon 7 . Also, as with bioenergy crops, it is difficult, if not impossible, to reliably quantify the effects of future climate change during 2050-2100.…”
Section: Scrutinize Co 2 Removal Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Counter-intuitively, afforestation at mid-latitudes and in northern, boreal forests may have a net warming effect, despite increasing the storage of carbon 7 . Also, as with bioenergy crops, it is difficult, if not impossible, to reliably quantify the effects of future climate change during 2050-2100.…”
Section: Scrutinize Co 2 Removal Methodsmentioning
confidence: 99%
“…It has fallen to other groups to review insights and gaps in our understanding of the influence of CO 2 -removal techniques on ecology [3][4][5] ; to make broad assessments of climate-engineering schemes 6 ; and to carry out comparative modelling studies 7 .…”
mentioning
confidence: 99%
“…In the period 2020-2100, we undertook a number of AOA experiments using a fixed quantity of 0.25 Pmol yr −1 of alkalinity, a similar amount to that used by Keller et al (2014). Consistent with this study, we applied AOA in the surface ocean all year round in ice-free regions, set to be between 60 • S and 70 • N (note that this ignores the presence of seasonal sea ice in some small regions).…”
Section: Model Experimental Designmentioning
confidence: 99%
“…They estimated that to mitigate the associated 1.5 K warming difference, via reducing atmospheric CO 2 concentrations by ∼ 400 ppm, an addition of 114 Pmol of alkalinity (between 2018 and 2100) would be required, and it would come at the cost of very large (unprecedented) changes in ocean chemistry. Keller et al (2014) used an Earth system model of intermediate complexity (EMIC) to explore the impacts of AOA over the period 2020-2100 arising from a globally uniform addition of alkalinity (0.25 PmolALK yr −1 ), an amount based on the estimated carrying capacity of global shipping following Kohler et al (2013). Keller et al (2014) showed that AOA led to a reduction in atmospheric CO 2 of 166 PgC (or ∼ 78 ppm), a net surface air temperature cooling of 0.26 K and a global increase in ocean pH of 0.06 in the period 2020-2100.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation